Compound 7 regulates microglia polarization and attenuates radiation-induced myelopathy via the Nrf2 signaling pathway in vivo and in vitro studies - Han Wu; Jianping Wu; Jianzhuo Jiang; Zeyu Qian; Shuang Yang; Yanze Sun; Hongxia Cui; Shengwen Li; Peng Zhang; Zhiqiang Zhou (Molecular Medicine)
Abstract Background Radiation-induced myelopathy (RM) is a significant complication of radiotherapy with its mechanisms still not fully understood and lacking effective treatments. Compound 7 (C7) is a newly identified, potent, and selective inhibitor of the Keap1-Nrf2 interaction. This study aimed to explore the protective effects and mechanisms of C7 on RM in vitro and in vivo. Methods Western blotting, quantitative real‐time polymerase chain reaction (qRT‐PCR), reactive oxygen species (ROS) and mitochondrial polarization, terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay, genetic editing techniques, locomotor functions, and tissue staining were employed to explore the protective effects and underlying mechanisms of C7 in radiation-induced primary rat microglia and BV2 cells, as well as RM rat models. Results In this study, we found that C7 inhibited the production of pro-inflammation cytokines and oxidative stress induced by irradiation in vitro. Further, the data revealed that radiation worsened the locomotor functions in rats, and C7 significantly improved histological and functional recovery in RM rats. Mechanically, C7 activated Nrf2 signaling and promoted the microglia transformation from M1 to M2 phenotype. Conclusion C7 could ameliorate RM by boosting Nrf2 signaling and promoting M2 phenotype microglia polarization in vitro and in vivo.